Penegakan Hukum HAM di Indonesia dalam Perspektif Paradigma Keadilan Hukum Transendental - Ni Nyoman Putri Purnama Santhi; Yudi Gabriel Tololiu; Bayu Anggara (DOKTRINA: JOURNAL OF LAW, 2023)
This research discusses how law enforcement is in Indonesia, and how does the law enforcement is in the perspective of a transcendental justice paradigm. This research is a library research using secondary data sources, namely primary and secondary legal materials. This research includes normative research with a synthetic analytic approach. Based on the results of the analysis, law enforcement in Indonesia, both criminal and civil, is still fixated on legal certainty, thus ignoring substantive justice. This is where a shift is needed from the law enforcement paradigm based on legal certainty to transcendent justice. This condition can be seen from several decisions that are very formalistic and based on laws, where legal certainty is at the forefront compared to substantive justice so that justice is not felt by the community. This condition is also strongly influenced by the legal paradigm adopted in Indonesia, namely positivist law or known as the systemic legal paradigm. Transcendental starts from irrational and metaphysical thoughts such as emotions, feelings, instincts, moral spirituality and as part of the science of building. In this context, law enforcement. The perspective of the paradigm of transcendental legal justice highlights how the objectives of Islamic law are beneficial to justice and human welfare. Where law is based on ethics (moral) so that it can produce substantive justice, not mere formalistic justice, which encapsulates human attitudes to be fair to God as the creator, fair to fellow human beings and fair to the universe.